2019
DOI: 10.1111/fmii.12112
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of problem loans on Japanese bank productivity growth?

Abstract: This paper examines for the first time the impact of problem loans on Japanese productivity growth. We exploit a new data set of Japanese problem loans classified into two categories: bankrupt and restructured loans. We opt for a novel and flexible productivity growth decomposition that allows to measure the direct impact of these problem loans on productivity growth. The results reveal that Japanese bank productivity growth was severely constrained by bankrupt and restructured loans early in 2000s, whilst som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 95 publications
(207 reference statements)
0
8
0
Order By: Relevance
“…The impact of capitalization on efficiency is presented with mixed evidence. Conditional on a model specification, Mamatzakis et al (2019) found both positive and negative associations between capitalization and efficiency for a sample of Japanese banks. In the study of 10 European banking systems, Lozano-Vivas et al (2002) found that capital ratio is important for explaining efficiency differences for banks in the U.K. and France.…”
Section: Variables For Explaining Inefficiency In Bankingmentioning
confidence: 95%
See 1 more Smart Citation
“…The impact of capitalization on efficiency is presented with mixed evidence. Conditional on a model specification, Mamatzakis et al (2019) found both positive and negative associations between capitalization and efficiency for a sample of Japanese banks. In the study of 10 European banking systems, Lozano-Vivas et al (2002) found that capital ratio is important for explaining efficiency differences for banks in the U.K. and France.…”
Section: Variables For Explaining Inefficiency In Bankingmentioning
confidence: 95%
“…The bank is viewed as a DMU which collects deposits with labor and capital and produces loans and other earning assets (Sealey Jr. and Lindley (1977)). Application examples of this approach include analysis at the bank level and can be found in Aly et al (1990), Isik and Hassan (2002), Casu et al (2013), Almanidis et al (2019), Mamatzakis et al (2019), to mention a few.…”
Section: Sensitivity To Market Riskmentioning
confidence: 99%
“…For simplicity, we name these two types of problem loans as bankrupt loans (BRL) and restructured loans (RSL) thereafter. Such disaggregation of problem loans has not been employed widely in the Japanese banking productivity literature (Mamatzakis et al, 2016). This disaggregation allows us to explore the extent to which each uncontrollable input, namely bankrupt loans and restructured loans, affects bank productivity.…”
Section: Datamentioning
confidence: 99%
“…Moreover, in Japanese banking literature, bank efficiency studies have dominated the research field of bank performance, for example Drake and Hall (2003), Fukuyama and Weber (2005), Fukuyama and Weber (2010), Barros, Managi, and Matousek (2012), Yang and Morita (2013). Japanese bank productivity has been rather neglected (Assaf, Barros, & Matousek, 2011;Fukuyama, 1995;Fukuyama, Guerra, & Weber, 1999;Mamatzakis et al 2016;Mamatzakis and Koutsomanolis-Filippaki, 2009). We, thus, fill a gap in the literature and apply for the first time a productivity growth decomposition to Japanese banks, where problem loans' impact would be revealed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation